Sunzen To Make Food Safer For Consumption - It is also developing non antibiotic animal feed additives - The Star, Rachael Kam (2008)
ANIMAL biotechnology specialist and feed additives manufacturer Sunzen Biotech Bhd plans to develop more green or non antibiotic animal healthcare products to improve food safety for consumers.